Psalm 78: A Case Study in Redaction as Propaganda - Tammuz, Oded (The catholic biblical quarterly, 2017)
The original version of Psalm 78 was written in the northern kingdom. Its original purpose is not known, but its topic is clear: God's continued benevolence to the people of Israel despite their disobedience and disloyalty. During the reign of King Zedekiah of Judah (597–586 b.c.e.), there was, on one side, a faction that advocated rebelling against the Babylonians and, on the other side, people such as the prophet Jeremiah who argued against rebelling. A member of the former faction (the redactor of Psalm 78) took it upon himself to write a document that would support his side. The basis of the new document was the original version of Psalm 78, which was widely known in Judah. The redaction included additions and alterations on a very small scale (vv. 4a and 9-10 were added, and vv. 67-71 were altered). Two methods were used in the redaction: (1) working from the outside inward, and (2) détournement. The secondary purpose of the redaction was to explain v. 57b, which the redactor did not understand.